Meningkatkan Kemampuan Ekstrakurikuler Pencak Silat Melalui Multimedia Interaktif Pada Anak Disabilitas Rungu (Penelitian Tindakan Kelas VIII di SLB N 2 Pariaman) - Salsabil, Camila Zesi; Budi, Setia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research was motivated by the problems found in SLBN 2 Pariaman class VIII/B. There were two students who had problems in extracurricular pencaksilat learning where the teacher had not used learning media. To overcome this problem, the researcher used multimedia media to improve extracurricular pencak silat skills for hearing impairments. In this study, the method used was classroom action research consisting of II cycles. Each cycle consists of four face-to-face meetings and each learning activity is evaluated. The cycles are carried out in several stages, namely planning,implementing actions, observation and reflection. The results of this study indicate that the process of extracurricular pencak silat learning using multimedia media for children with hearing impairments in class VIII/B has increased using multimedia media. This can be seen from the initial condition of the child before being given R 36,78% and I 37,35% action, while at the end of cycle I the child's ability increased to R 75% and I 71.66%, in cycle II the ability R 96.66% and I 95%. So it can be concluded that the implementation of extracurricular pencak silat learning using multimedia media has increased.